2019
DOI: 10.1253/circj.cj-19-0125
|View full text |Cite|
|
Sign up to set email alerts
|

Survey of Palliative Sedation at End of Life in Terminally Ill Heart Failure Patients ― A Single-Center Experience of 5-Year Follow-up ―

Abstract: Based on a review of Palliative Care Team consultations, patients who were hospitalized for HF and died during the hospitalization despite optimal pharmacological and/or nonpharmacological therapy were selected and defined as terminally ill HF patients. We excluded patients who were intubated or receiving mechanical circulatory support at the time of death. Patients who were administered intravenous sedation within the last week at life were defined as patients receiving palliative sedation 4 and were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…15 The majority of studies were conducted in palliative care services. Eight articles included sedated patients with non-malignant disease, 2,8,10,17,31,32,34,45 three did not specify a diagnosis 4,24,42 and the rest included only cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The majority of studies were conducted in palliative care services. Eight articles included sedated patients with non-malignant disease, 2,8,10,17,31,32,34,45 three did not specify a diagnosis 4,24,42 and the rest included only cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported assessment of vital signs when presenting their results on palliative sedation. 6,44,45…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deksmedetomidyna stosowana jest również w sedacji u chorych wentylowanych mechanicznie, można ją bezpiecznie stosować również w bezpośrednim okresie po ekstubacji. Do rozważenia jest jej użycie w czasie procedur chirurgicznych, gdy waż-na jest współpraca chorego z lekarzem przy jednoczesnym zachowaniu świadomości [23,24].…”
Section: Pozarejestracyjne (Off-label) Zastosowanie Deksmedetomidyny ...unclassified
“…6,14 The evidence for its efficacy in palliative care is more limited 11 with case reports for its use showing positive analgesic benefits in advanced cancer 15,16 and a retrospective chart analysis showing a benefit in the treatment of delirium in patients with cardiac disease. 17 Hofherr et al 18 report on two cases of its use in terminal delirium using an adapted ICU protocol, without cardiac monitoring on an inpatient palliative care ward. These promising results, as well as the characteristics of reduced delirium and increased rousablility, make dexmedetomidine a potentially favourable option for managing confusion and pain at the end of life.…”
Section: Introductionmentioning
confidence: 99%